2021
DOI: 10.1186/s43044-021-00221-1
|View full text |Cite
|
Sign up to set email alerts
|

Time to think beyond door to balloon time: significance of total ischemic time in STEMI

Abstract: Background Significance of total ischemic time (TIT) in the context of ST-segment elevation myocardial infarction (STEMI) is still controversial. Therefore, in this study, we have evaluate the association of TIT with immediate outcomes in STEMI patients in whom recommended door to balloon (DTB) time of less than 90 min was achieved. Results A total of 5730 patients were included in this study, out of which 80.9% were male and median age was 55 [61–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Numerous studies have demonstrated the connection between TIT and the prognosis following PCI in patients with STEMI [16,22]. This study's key conclusion was the identification of a direct link between TIT and various in-hospital complications, such as pulmonary edema and cardiogenic shock.…”
Section: Discussionmentioning
confidence: 79%
“…Numerous studies have demonstrated the connection between TIT and the prognosis following PCI in patients with STEMI [16,22]. This study's key conclusion was the identification of a direct link between TIT and various in-hospital complications, such as pulmonary edema and cardiogenic shock.…”
Section: Discussionmentioning
confidence: 79%
“…The duration of ischemia was demonstrated to be a major predictor of poor clinical outcomes in large therapeutic trials in STEMI patients utilising either thrombolysis or primary PCI 33 . Even when the optimal door‐to‐balloon time was met in a prior trial, a longer ischemia duration was associated with higher in‐hospital mortality 34 …”
Section: Discussionmentioning
confidence: 99%
“…In this prospective study, we endeavored to assess the association of TIT with clinical outcomes in STEMI patients undergoing PCI and observed that the mortality rates were higher with prolonged TIT during the hospital stay and at one-year follow-up, but the values were not statistically significant. The high mortality with prolongation of ischemic time may be due to the fact that infarct size significantly affects myocardial tissue and continues to damage with each passing second of ischemic time [8][9][10][11]. As a result, even with optimal reperfusion (primary PCI), prolonged ischemic time may result in increased mortality as well as decreased myocardial salvage [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…The high mortality with prolongation of ischemic time may be due to the fact that infarct size significantly affects myocardial tissue and continues to damage with each passing second of ischemic time [8][9][10][11]. As a result, even with optimal reperfusion (primary PCI), prolonged ischemic time may result in increased mortality as well as decreased myocardial salvage [11][12][13]. In this study, there were two (2.4%) cardiac deaths with prolonged TIT during the hospital stay, and this value was 6 (7.2%) at one-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation